Psychological mechanisms of group influence on individual behavior - S. A. Ganat (Вестник университета)
The paper analyzes psychological mechanisms of group influence on individual behavior, including conformity, social suggestion, authority pressure, and imitation, which have a decisive influence on individual behavior formation in social groups. Special attention has been paid to these mechanisms’ transformation under the influence of digital media and new communication technologies in the context of globalization. Digital platforms influence on the political activity of young people has been studied, which emphasizes the increasing role of online communications in shaping group behavior. Group norms and expectations, often imposed through digital platforms, actively shape social identity and individuals’ behavior, increasing their susceptibility to group pressure and conformity. Leadership styles have also been found to significantly influence group dynamics by altering group members’ behavioral responses. Cross-cultural studies show the importance of contextualization, as responses to social pressure vary across cultures. There is a need for further research on the long-term effects of social influence and the development of methods to minimize its negative effects on individual behavior. The study results contribute to a deeper understanding of the social influence mechanisms in the context of globalization, noting the importance of an interdisciplinary approach.